Profit maximization techniques for operating chemical plants - Lahiri, Sandip Kumar, 1970- (John Wiley & Sons, Inc., 2020)
"Profit maximization is at the core of every chemical company's vision and mission nowadays. Making money by safely producing chemicals, sailing locally are no more adequate to survive in today's business environment. Maximization of profit, continuous improvement of operation, sustainability, enhanced reliability to reduce production cost are buzzwords in today's CPI. Industries are slowly shifting their priority to energy efficiency, real-time process optimization, environment friendliness, and sustainability. Running the plant at their highest feasible capacity by exploiting the margin available in process equipment is no longer a luxury but a necessity. There is a drastic change of business environment in last 20 years. Shrinking profit margin of chemical process industries (CPI) due to globalization, uneven label playing field in international chemical business give rise to cut-throat competition among process industries has changed the global chemical business scenario(Lahiri, 2017b)"--